Anggaran Penjualan Sebagai Alat Bantu Manajemen Dalam Pengelolaan Laba Perusahaan - Asrani Sinaga; Ova Novi Irama (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2021)
This study aims to determine whether the sales budget can be used as a management tool in managing company profits and to determine the extent to which the sales budget can be used as a management tool in managing company profits at PT. Sari Incofood Corporation. The research method used in this research is descriptive qualitative research, with secondary data. From the research results obtained that the use of the sales budget at PT. Sari Incofood Corporation has not been fully able to become a management tool in managing company profits. Where the Indocafe Maxtea product in 2017, 2018, 2019 and the Indocafe Cappuchino product in 2017 can still earn a profit between the cost of production and the realization of sales with a total of Rp. 11,660,000,000 (Favourable Variable). However, Indocafe Cappuchino products in 2018 and 2019 still have a disadvantageous difference or cannot earn a profit between the total cost of production and actual sales with a total of Rp.785,000,000 (Unfavourable Variable).